2018
DOI: 10.3390/ijerph16010079
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the Development of a Food Stress Index to Identify Households Most at Risk of Food Insecurity in Western Australia

Abstract: Food stress, a similar concept to housing stress, occurs when a household needs to spend more than 25% of their disposable income on food. Households at risk of food stress are vulnerable to food insecurity as a result of inadequate income. A Food Stress Index (FSI) identifies at-risk households, in a particular geographic area, using a range of variables to create a single indicator. Candidate variables were identified using a multi-dimensional framework consisting of household demographics, household income,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Government monitoring and surveillance systems, independent of the food industry and the charitable food sector should be developed to contribute country level information to inform appropriate actions. At a minimum these should include using standardised and robust measures of: household food and nutrition security that captures severity and prevalence and includes children (e.g., the United States Department of Agriculture (USDA)’s 18 item U.S. Household Food Security Survey Module where appropriate or part of the suite [64]); food related measures of financial stress (e.g., food stress [65]); routine measure of dietary intake, measured height and weight, and socioeconomic status; and food assistance services performance indicators. Collectively these build information and intelligence systems to inform the delivery of targeted food insecurity interventions.…”
Section: What Should or Could Be Done And By Whommentioning
confidence: 99%
“…Government monitoring and surveillance systems, independent of the food industry and the charitable food sector should be developed to contribute country level information to inform appropriate actions. At a minimum these should include using standardised and robust measures of: household food and nutrition security that captures severity and prevalence and includes children (e.g., the United States Department of Agriculture (USDA)’s 18 item U.S. Household Food Security Survey Module where appropriate or part of the suite [64]); food related measures of financial stress (e.g., food stress [65]); routine measure of dietary intake, measured height and weight, and socioeconomic status; and food assistance services performance indicators. Collectively these build information and intelligence systems to inform the delivery of targeted food insecurity interventions.…”
Section: What Should or Could Be Done And By Whommentioning
confidence: 99%
“…A diet was deemed to be unaffordable if it cost more than 30% of household income (7). If the diet cost more than 25% of disposable household income, the household was considered to be in food stress (17,31).…”
Section: Analysis and Reportingmentioning
confidence: 99%
“…The absence of robust food insecurity monitoring and surveillance systems in the households of Australia, Scotland and Europe has led researchers to undertake a secondary analysis of related surveys, such as Scotland’s Living Costs and Food Survey [14] and Australia’s Household Expenditure Survey [6], in order to determine the nature and prevalence of household food insecurity [15]. Food affordability, a key component of food security, has been determined using comparisons of the weekly food expenditure and its ratio to equalized income for households with varying income levels in Scotland [14] and Australia [16,17]. Analysis trends in the relationship between food affordability at the household level and diet quality in Scotland found that poorer households were less likely to achieve recommended dietary intakes over time [14].…”
Section: Measurement and Monitoringmentioning
confidence: 99%
“…The same questions are being asked in Australia and New Zealand in the absence of robust and comprehensive food insecurity monitoring systems. Similar to the concept of rental stress, the innovative geographically based Food Stress Index was developed using the Western Australian Government’s Food Access and Cost Surveys and relevant sociodemographic census data to determine place-based risk of food stress [16]. Emergency relief service providers and government policy makers are very interested in applying the FSI to identify areas of particular need for food security action.…”
Section: Measurement and Monitoringmentioning
confidence: 99%